J.CO Coffee & Donuts Marketing Strategy - Putri, Aulia Riski Ayu; Nisa, Indah Khoirun; Yee, Lim Hui; Kee, Daisy Mui Hung; Min, Koo Hui; Yi, Lee Sing; Xin, Liu Jie (Asia Pacific Journal of Management and Education (APJME), 2020)
J. CO Donuts & Coffee is a franchise of café restaurant chains that sell donuts, coffee and frozen yogurt. The company is owned by Johnny Andrean Group. Since 2005, J.CO Donuts & Coffee becomes the fastest growing donut & coffee chain in Indonesia. They have successfully penetrated into the local market in Indonesia against Krispy Kreme and Dunkin Donuts. They also have been rapidly expanding their store chains throughout South East Asia countries such as Malaysia, Singapore, Philippines, and Hong Kong. Analysis of J.CO Donuts & Coffee will be done to know more on the position of the company in the market. SWOT analysis is needed to know JCO Donuts & Coffee marketing situation.